Developing Learning Tools of Long Jump Hang Style in Vocational High Schools Through Problem-Based Learning Approaches - Listiono, Bernaditya; Winarni, Sri (Universitas Negeri Semarang (Unnes), 2019)
This study aimed at describing: 1) validity, 2) practicality, and 3) effectiveness of long jump hang style learning tools in vocational high schools through problem-based learning approach in terms of the learning outcomes and attitudes towards physical education learning. This research used the 4D model development research. The product trials were conducted in SMK N 1 Cangkringan at X class of APHP 1 and APL 1. The instruments employed 3 types to measure: a) its validity, b) its practicality, and c) its effectiveness. The results of the research showed that 1) the long jump hang style learning model with the problem-based learning approach in the form of syllabus, lesson plans, worksheets, and evaluation instruments respectively fulfilled the category of â€œvery validâ€. 2) The learning tools also fulfilled the category of â€œvery practicalâ€. 3) The passing rate of learning outcomes reached more than 75% in X class of APHP 1 and 80.65% in APL class X 1. The studentsâ€™ attitudes towards physical education learning obtained the high minimum category of more than 80%, namely for X class of APHP 1 and 90.32% for class X APL 1. Thus, the device can be declared as effective based on the learning outcomes and attitudes towards physical education learningÂ